(3TQM GdecJSH aj UfGYI RQGYI GdPgHs - (3GdLdOcj, YR GdOjf, Ydj Hf eMeO Hf CjOeQ, J HYO (B742 (3g`s
(3ChdgG (B:s
(3HSe Gddg bGd GdYdGeI GdjdSha UGMH cJGH GdecJSH aj UfGYI RQGYI GdPgH HYO NWHI cJGHg hHYO aEfj UfYJ gPG GdcJGH PGcQG ajg Yde UfGYI GdcjejGAs
(3BNQgG (B:s
(3Gdb Ydj YTQI ef GdRGL GdPGFH jQLY eGA aCdb Ydjg bdjd hYTQI ef GdCHb GdeWgQI jfYbO hCda hGMO Ydi YTQ ef OgQI eWgQI jbhe beQG Ef TGA Gddg JYGdis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\5s
(3cTa GdXfhf (B2\1811s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdcjejGA hGdWHjYjGJs